Eligibility for sacubitril–valsartan in patients with acute decompensated heart failure - David Carballo; Jérôme Stirnemann; Nicolas Garin; Chistophe Marti; Jacques Serratrice; Sebastian Carballo (ESC Heart Failure)
Abstract Aims Large‐scale clinical trials have demonstrated clinical benefits of sacubitril–valsartan in symptomatic heart failure with reduced ejection fraction patients (PARADIGM‐HF), with potential benefits in patients hospitalized for acute decompensated heart failure (ADHF) (PIONEER‐HF) and fewer benefits in patients with heart failure with preserved ejection fraction (PARAGON‐HF). The aim of this study was to evaluate eligibility for sacubitril–valsartan using criteria described in PIONNER‐HF in non‐selected patients hospitalized for ADHF. Methods and results Between November 2014 and May 2019, 799 patients were recruited in a prospective registry of acute heart failure at the University Hospitals of Geneva (ClinicalTrials.gov: NCT02444416). The cohort consists of consecutive patients admitted to the Department of Medicine with ADHF. Eligibility for sacubitril–valsartan was determined using criteria described in PIONEER‐HF, including left ventricular ejection fraction, clinical parameters, and co‐morbidities. Of 799 patients, 123 (15.39%) were eligible for sacubitril–valsartan treatment. Clinical outcomes including all‐cause mortality and readmission were similar in eligible and non‐eligible groups, hazard ratio 1.02 (95% confidence interval 0.81–1.29, P = 083). Conclusions Using current criteria from randomized controlled trials, only 15% of non‐selected patients admitted for ADHF are theoretically eligible for sacubitril–valsartan. Eligibility for sacubitril–valsartan using published criteria is not associated with worse outcome, suggesting that further evaluation of benefits of sacubitril–valsartan in heart failure patients based on parameters other than left ventricular ejection fraction may be of interest.